EFFECT OF TEMPERATURE AND pH OF MODIFICATION PROCESS ON THE PHYSICAL-MECHANICAL PROPERTIES OF MODIFIED CASSAVA STARCH - Yudi Wicaksono; Nuri Nuri; Budipratiwi Wisudyaningsih (Molekul, 2016)
The use of cassava starch for excipient in the manufacturing of the tablet has some problems, especially on physical-mechanical properties. The purpose of this study was to determine the effect of the differentness of temperature and pH in the process of modification on the physical-mechanical properties of modified cassava starch. Modifications were performed by suspending cassava starch into a solution of 3 % (w/v) PVP K30. The effect of the difference of temperature was observed at temperatures of 25; 45 and 65 0C, while the effect of the difference of pH was observed at pH of 4.0; 7.0 and 12.0. The results showed that the temperature and pH did not affect the physical-mechanical properties of the modified cassava starch. Modification of cassava starch at pH and temperature of 7.0 and 45 0C was produced modified cassava starch with the most excellent solubility, while the best swelling power were formed by the modification process at pH and temperature of 7.0 and 25 0C. Overall, the most excellent compression properties of modified cassava starch resulted from the modification process at pH 12.